Quality of Care for Patients with ST-Segment Elevation Myocardial Infarction in Chaophya Hospital, Bangkok - Duangdech, Wanid; Dutsadeevettakul, Somchai (Journal of Health Science of Thailand, 2017)
The aim of this study was to determine the quality of care for patients with ST Segment elevation myocardial infarction in Chaophya hospital. Data were retrospectively collected from the medical records of all patients with the diagnosis of STEMI from January 2001 to June 2007. The results revealed that 64 patients were eligible for the study. Of these, 57 patients (89.1%) received a reperfusion therapy, 30 patients undergoing fibrinolytic therapy and 27 patients percutaneous transluminal coronary angioplasty. Of all the total number that received treatment, there were no fatalities in the hospital that were recorded. The median door-to-needle time for fibrinolytic therapy was 60 minutes (mean =78.53, SD = 63.24, median = 60, Q1=45, Q3= 87.75). The median door- to-balloon time was 80 minutes (mean =89.81, SD = 40.42, median = 80, q1=55, q3= 120). Time to reperfusion therapy, door-to-needle time and door-to-balloon time, were not statistically different when comparing between the period prior to (January 2001 to August 2004) and after (September 2004 to June 2007) as the 24-hours heart center service became operational with availability of round-the-clock, in-house cardiologist. The study demonstrated acceptable door-to-balloon time of less than 90 minutes, but delayed door-to-needle time of more than 30 minutes. This was due to time loss in decision making by patients, care process, consultation by ER physicians and delayed diagnosis at initial evaluation. Since the data were retrospectively collected from medical records and had sample size limitation, a prospective study may lead to a more reliable conclusion.